Homosexual society - Hauser,Richard (London, 1962)
At the beginning of the text we refer to the cause of our inquiry into the Homosexual Society. Before we started work we decided that this was a department of life which in recent years had been brought much more into the light of day but that, nevertheless, much misery and unhappiness was still being endured by many people through misunderstanding and prejudice. Public tolerance is, perhaps, greater on account of the many inexpensive text books on this subject produced since the war and the greater use of this choice in literature. The Kinsey report and the Wolfenden report have both appeared. But the extent of the problem is in doubt and, since this is not a matter of statistical returns, must for long remain in doubt.
Keywords: Sociology